Flavor Oscillation of Neutrino with Mass Matrix - Powrel, Jhulan (Himalayan Physics, 2013)
There is evidence that atmospheric, solar, accelerator, and reactor neutrinos changes from one flavor to another as observed in experiment.MiniBooNE and KamLAND are experimental set up used for their observations. Thus it is obvious that neutrino have mass hierarchy with changing flavor. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 83-86 Uploaded date: 12/23/2013